The factor effectiveness of ACD implementation for SKG 19: project management Petronas Carigali Sdn. Bhd. / Muhammad Shaazrai Kamin - Kamin, Muhammad Shaazrai (Faculty of Business and Management, 2014)
Petroliam Nasional Berhad (PETRONAS) is a one of the nation proud. With a twin skyscraper in the middle of the city, it monitors and handles the whole business regardless the business from upstream or downstream. It is the centre where decision is made. As the business goes global, competition is an external factor that cannot be avoided. Wherever the business operates, there would be the rivals coming in the competition. Thus, strategists have to work more on the way forward to overcome the matter. Another challenge faced by the oil and gas industry this year is the drop price of the oil. The price becomes cheaper according to the world price and it resulted in the lower margin of the revenue. Thus, many aspects need to be improvised including in an aspect of staffs’ capability on doing work. To ensure the competencies of Petronas’ engineers, Accelerated Capability Development (ACD) program was introduced in 2008. This is purposely to create a systematic process of job and salary grade whereby the engineers will go through one by one stage according to the level of expertise. What is more strategic on this process is that the engineers would be tested by the assessment in order to increase their job and salary grade. Coaching and training also provided as the essential programs in the ACD program. The research is focusing on Accelerated Capability Development (ACD) process at PETRONAS Carigali Sdn. Bhd., in Surface Engineering and Project Management department which specifically in a skill group 19: Project Management. The theoretical framework of this study consists of dependent variable and independent variables. The sample size of this study was 60. Data was obtained using primary and secondary data. Respondents were required to answer the questionnaires that included the statements of each variable. Once the necessary data was collected, the data was analyzed and summarized in a readable and easily interpret form. The Statistical Package for the Social Science (SPSS) version 20.0 was used to summarize the data.